On The Modification of Richards Modulus of Rupture Equipment - Agrawal, R P; Sharma, D P (Annals of Arid Zone, 2016)
Richards modulus of rupture equipment was modified and fabricated from indigenous materials. An excellent agreement between the modulus of rupture values with the Richards equipment and modified equipment was obtained. The modified equipment exhibited better reproducibility (coefficient of variation lower than Richards equipment) and was suitable even for low strength soils. The equipment has applications in soil physics and soil mechanics. The equipment is cheap, simple in operation, and can easily be manufactured.